DAMPAK MERKURI TERHADAP LINGKUNGAN PERAIRAN SEKITAR LOKASI PERTAMBANGAN DI KECAMATAN LOLODA KABUPATEN HALMAHERA BARAT PROVINSI MALUKU UTARA - Guntur Ekaputra Bernadus; Bobby ., Polii; Johnly Alfred Rorong (Sam Ratulangi University, 2021)
This study aims to assess the potential impact of mercury pollution in the Tiabo waters (river) which is located in the gold mining location without permission from Bakun Pantai Village, Loloda District, West Halmahera Regency, North Maluku Province. This research was conducted in July - December 2020. The analysis of research data was carried out in a descriptive way by looking at the results of the measurement results of the mercury sample test in water then comparing with the environmental quality standards according to PP No. 82 of 2001 class II concerning Water Quality Management and Water Pollution Control. Whereas mercury in sediment is compared with the quality standard for heavy metal concentrations in IADC / CEDA 1997. The samples used in this study were river water and sediment (silt at the bottom of the river). Water and sediment samples were taken from the upstream, middle and downstream of the river. The results of the examination of Hg levels in water samples at the upstream, middle and downstream locations showed that the results were <0.0005 mg / L, the lowest pH was 7.57 and the highest was 7.84 n / a, the lowest DO was 8.13 mg / L, the highest was 8.21 mg / L. The results of measurements of mercury levels in the sediment of the Tiabo river in Bakun Pantai Village, Loloda District, West Halmahera Regency which were carried out at three points, namely upstream, middle and downstream of the river, the value of mercury content in the upstream river was 1.35 mg / L, in the middle it was 0.47. mg / L, and downstream of <0.05 mg / L.Â